Cabazitaxel Induced Thrombotic Microangiopathy in a Patient with Prostate Cancer. (19th November 2019) - Nlandu, Yannick; Pourcine, Franck; Vong, Ly van phach; Chelly, Jonathan; Jochmans, Sebastien; Mazerand, Sandie; Monchi, Mehran
Abstract : Cancer-associated thrombotic microangiopathy (TMA) refers to a group of disorders characterized by microangiopathic haemolytic anemia, thrombocytopenia, and ischemic organ damage. TMA manifestations can be induced by cancer or by chemotherapy. We report the case of a 64-year-old man with metastatic prostate cancer who experienced a Cabazitaxel-induced TMA manifestation. TMA responds to conservative therapy, dialysis without plasmaphoresis, with progressive recovered renal function.